2015
DOI: 10.1002/clc.22418
|View full text |Cite
|
Sign up to set email alerts
|

Survivors of Aortic Dissection: Activity, Mental Health, and Sexual Function

Abstract: Background: Currently no research exists assessing lifestyle modifications and emotional state of acute aortic dissection (AAD) survivors. We sought to assess activity, mental health, and sexual function in AAD survivors. Hypothesis: Physical and sexual activity will decrease in AAD survivors compared to pre-dissection. Incidence of anxiety and depression will be significant after AAD. Methods: A cross sectional survey was mailed to 197 subjects from a single academic medical center (part of larger IRAD databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 17 publications
4
55
3
Order By: Relevance
“…Postoperative health-related quality of life (HRQoL) in operated ATAAD patients has been reported to be significantly lower than in the general population [112][113][114]. Furthermore, HRQoL has been shown to decline over time [112] and there is a 32% incidence of ATAAD patients suffering from episodes of depression; up to 32% are at risk of post-traumatic stress disorder and ATAAD patients have reported that they have reduced sexual activity [115]. Clearly, patients who have undergone surgery for ATAAD have an increased risk of psychiatric morbidity, and screening for psychiatric disease and factors related to poor HRQoL may therefore be considered.…”
Section: Outcome and Long-term Follow-upmentioning
confidence: 99%
“…Postoperative health-related quality of life (HRQoL) in operated ATAAD patients has been reported to be significantly lower than in the general population [112][113][114]. Furthermore, HRQoL has been shown to decline over time [112] and there is a 32% incidence of ATAAD patients suffering from episodes of depression; up to 32% are at risk of post-traumatic stress disorder and ATAAD patients have reported that they have reduced sexual activity [115]. Clearly, patients who have undergone surgery for ATAAD have an increased risk of psychiatric morbidity, and screening for psychiatric disease and factors related to poor HRQoL may therefore be considered.…”
Section: Outcome and Long-term Follow-upmentioning
confidence: 99%
“…However, patients with aortic dissection need complete bed rest for at least 48 h after onset because there is an increased risk of aortic rupture [1], and there is little evidence of the influences of physical activity and exercise after the period of complete bed rest. It has previously been reported that patients tended to be short of exercise and depressed after aortic dissection, and there was a possibility that forced bed rest without an underlying rationale might have caused patients to become anxious [18]. In our clinical practice, we encountered patients with conservatively treated aortic dissection who became aware of reduced physical strength as the degree of bed rest became less strict, and became depressive due to anxiety about economic issues or return to work [19].…”
Section: Discussionmentioning
confidence: 99%
“…For selected AD patients, returning to former occupational and leisure-time activities is an important objective and may also be psychologically therapeutic. Unfortunately, many of these patients fail to return to specifi c activities, including sexual activity ( 7 ), because they lack the medical assurance that they can resume these activities safely. Because advising the post-AD patient to return to high-volume, high-intensity activities is complex, it is important for physicians (and patients) to have as much information as possible about the associated myocardial and aerobic requirements.…”
Section: Invited Commentarymentioning
confidence: 99%
“…Because few data are available regarding the specifi c types and intensities of exercise that may be both safe and benefi cial for this escalating patient population, this void poses a conundrum for patients with a prior AD, as well as for clinicians caring for and counseling them. Consequently, following AD, physical inactivity and depression/anxiety generally increase, which further reduce functional capacity and/or quality of life in AD survivors ( 7 ).…”
mentioning
confidence: 99%